Brand attachment: a review and future research - Shimul, Anwar Sadat (2022)
This paper conducts an integrative review and provides a synthesisation of key themes in the brand attachment literature. A total of 171 papers were selected and analysed using a framework-based approach. In addition to exploring the theories and frameworks, this review summarises the contexts, antecedents, outcomes, mediators, and moderators of brand attachment. Based on the gaps identified in current studies, directions are provided for future brand attachment research. The review suggests that there are multiple directions in which to take the domain further. Theoretical underpinnings require conceptual clarity and consistency with attachment theory, and the development and validation of research frameworks are essential. Furthermore, the application of contextual measurements and rigorous methodologies is warranted to address the shortcomings of the current literature. The recommendations of this review are expected to facilitate advancements in brand attachment research.